2007
DOI: 10.1128/jvi.00753-07
|View full text |Cite
|
Sign up to set email alerts
|

Studying Hepatitis C Virus: Making the Best of a Bad Virus

Abstract: 2An estimated 3% of the world population is infected with hepatitis C virus (HCV) (5,232). In most infected individuals, this remarkable RNA virus evades the immune system and establishes a chronic infection that can lead to cirrhosis, liver cancer, and death. While advances have been made in treating HCV, the current therapy, a combination of pegylated alpha interferon and ribavirin, is poorly tolerated and is effective in only 50% of genotype 1-infected patients (reviewed in reference 53). The quest for new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
98
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 256 publications
(285 reference statements)
3
98
0
6
Order By: Relevance
“…From these, SLIII is proposed to interact with the 40S ribosomal subunits thus playing a key role in translation initiation. The SLII and SLIII stem loops function in replication as well (13,15). Electromobility shift analysis showed that the SLIII was both necessary and sufficient for binding of the LSm1-7 ring to the 5ЈUTR region (Fig.…”
Section: Depletion Of the Proteins Dcp2 And Xrn1 Does Not Affect Infementioning
confidence: 99%
See 1 more Smart Citation
“…From these, SLIII is proposed to interact with the 40S ribosomal subunits thus playing a key role in translation initiation. The SLII and SLIII stem loops function in replication as well (13,15). Electromobility shift analysis showed that the SLIII was both necessary and sufficient for binding of the LSm1-7 ring to the 5ЈUTR region (Fig.…”
Section: Depletion Of the Proteins Dcp2 And Xrn1 Does Not Affect Infementioning
confidence: 99%
“…The HCV 3ЈUTR consists of a variable region, a poly (U/UC) tract and a highly conserved terminal region termed 3ЈX tail that consists of 3 stem loop structures (13). Importantly, the 3ЈUTR is not only required for replication but also for efficient translation (16).…”
Section: Depletion Of the Proteins Dcp2 And Xrn1 Does Not Affect Infementioning
confidence: 99%
“…The HCV viral genome (ϳ9.6 kb) codes for a unique polyprotein of ϳ3000 amino acids (recently reviewed in Refs. [2][3][4]. Following processing via viral and cellular proteases, this polyprotein gives rise to at least 10 viral proteins, divided into structural (core, E1, and E2 envelope glycoproteins) and nonstructural proteins (p7, NS2, NS3, NS4A, NS4B, NS5A, NS5B).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…HCV is a major cause of various liver diseases such as liver steatosis, fibrosis, and cirrhosis, which can eventually progress into hepatocellular carcinoma (2). HCV replicates within the ribonucleoprotein complexes assembled on the ER-derived membranous structures termed "membranous webs" (3)(4)(5). The translation of the positive-strand HCV RNA on the ER is facilitated by an internal ribosome entry site in its 5Ј-UTR, generating a 3000-amino acid polyprotein which is co-and post-translationally cleaved by viral and cellular proteases to yield structural and non-structural viral proteins (2,4).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…HCV replicates within the ribonucleoprotein complexes assembled on the ER-derived membranous structures termed "membranous webs" (3)(4)(5). The translation of the positive-strand HCV RNA on the ER is facilitated by an internal ribosome entry site in its 5Ј-UTR, generating a 3000-amino acid polyprotein which is co-and post-translationally cleaved by viral and cellular proteases to yield structural and non-structural viral proteins (2,4). HCV infection alters host lipid metabolism to facilitate enrichment of lipids that usually manifest in the accumulation of intracellular lipid droplets or hepatic steatosis (6 -8).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%